Effects of fly ash on the properties and microstructure of alkali-activated FA/BFS repairing mortar - Wang, Jixiang; Huang, Tianyong; Cheng, Guodong; Liu, Ze; Li, Siqi; Wang, Dongmin (Fuel (Guildford), 2019)
•The CAP and PSD of FA were defined as the major factors effecting properties of mortar.•The mechanical and bond strength depend more on CAP of FA.•The PSD of FA effected the flow value and shrinkage of mortar more apparently. This article presents the effects of fly ash (FA) on the properties and microstructures of alkali-activated FA/BFS repairing mortars. Firstly, the characteristics (chemical and mineral compositions, particle size distribution or specific surface area) of FAs were investigated. Two factors (the content of amorphous phases (CAP) and particle size distribution (PSD) or specific surface area) were defined as the two major variables and its effects on the properties (mechanical strength, flow value, and shrinkage) of alkali-activated FA/BFS repairing mortars were studied. The results indicated that the mechanical strength of alkali-activated FA/BFS mortar depended more on the content of amorphous phases since it facilitated the degree of geopolymerization reaction and the formation of products. IIFA/BFS exhibited the highest compressive, flexural, and interfacial flexural-tensile strength due to its higher content of amorphous phases. However, the particle size distribution of FA had little contribution on mechanical strength but effected the flow value and drying shrinkage more apparently. Additionally, it’s also found that except the mechanical interlocking and Van der Waals forces, the chemical bonding also presented between the repairing systems and substrate. That’s why the alkali-activated FA/BFS mortar exhibited higher bonding strength and was suitable for repairing concrete.